A Review on Rare Calciphylaxis Due to Primary Hyperparathyroidism - A. Mohamad Safwan; K. N. Vijayan (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
Calciphylaxis is a rare life-threatening condition characterized by progressive skin ischemia and extremely painful cutaneous necrosis and ulceration due to mural calcification and thrombosis of arterioles and capillaries in the dermis and subcutaneous adipose tissue. Most often this leads to sepsis and multi-organ failure with very high mortality. It is predominantly seen with end-stage renal disease (ESRD) patients who are on dialysis or who recently received a renal transplant. Therefore, it is associated with secondary or tertiary hyperparathyroidism. This entity termed uremic calciphylaxis. A similar rare entity in a patient with normal kidney function termed non-uremic calciphylaxis. Here we review a rare extensive presentation of calciphylaxis due to primary hyperparathyroidism with normal renal function. Calciphylaxis is a catastrophic disease that carries high morbidity and mortality due to sepsis and multi-organ failure A strong clinical suspicion should be kept in any patients with painful necrotic eschar with normal kidney function. Serum calcium and serum Parathyroid hormone should be screened in such cases. Early identification and prompt multi-disciplinary management are mandatory to improve survival.